Gambaran Pengetahuan Infeksi Menular Seksual pada Santri Pondok Pesantren Darul Hukumaini - Rosyunita, Rosyunita; Ayunda, Rahmah Dara; Elizar, Lale Justin Amelinda; Rahim, Adelia Riezka; Hasbi, Nurmi; Andrayani, Lale Wisnu (Universitas Mataram, 2024)
Adolescence is a time of curiosity about many things, including sexual behaviors that make it possible to become infected with sexually transmitted diseases. Education is needed to prevent transmission by providing material on the infections of reproductive organs. Based on this, this service aims to increase students' knowledge at the Pondok Pesantren Darul Hukumaini about the types of sexually transmitted infections and how to prevent them. The methods used for assessment were pre-test and post-test. Delivery of material was carried out using lecture and presentation methods to students. The participants were 32 aged 16-17 years and female. The assessment results showed an increase in students' scores from an average of 5.8 in the pre-test to 9.6 in the post-test. The lowest score obtained in the pre-test was 0 to 6.4 after the post-test or delivery of educational material. This increase in student's knowledge must be accompanied by habits of clean and healthy living behavior such as avoiding drugs and having free sex by the students themselves.